A disintegrin‐like and metalloproteinase with thrombospondin‐1 (ADAMTS‐1) levels in gingival crevicular fluid correlate with vascular endothelial growth factor‐A, hypoxia‐inducible factor‐1α, and clinical parameters in patients with advanced periodontitis. Issue 10 (28th May 2019) - Tayman, Mahmure Ayşe; Kurgan, Şivge; Önder, Canan; Güney, Zeliha; Serdar, Muhittin A.; Kantarcı, Alpdoğan; Günhan, Meral
Abstract: Background: ADAMTS (a disintegrin‐like and metalloproteinase with thrombospondin) are a family of proteinases that are structurally similar to the family of matrix metalloproteinases with critical roles in damage and repair of the extracellular matrix. Their functions are closely related to inflammation, hypoxia, and vascularization. Our aim was to determine levels of ADAMTS‐1 in gingival crevicular fluid (GCF) in patients with advanced periodontal diseases and identify their association with hypoxia‐inducible factor‐1alpha (HIF‐1α), vascular endothelial growth factor (VEGF‐A), and clinical parameters of periodontitis. Methods: The study consisted of three groups: healthy individuals (control; n = 20), generalized chronic periodontitis (CP; n = 21), and generalized aggressive periodontitis (GAgP; n = 20). Clinical parameters were measured. Levels of ADAMTS‐1, VEGF‐A, and HIF‐1α in GCF and serum were quantified by enzyme‐linked immunosorbent assay (ELISA) and reported as total amounts and concentration. Results: ADAMTS‐1 total amount in GCF were significantly higher in patients with CP and GAgP compared with healthy individuals ( P  < 0.05). HIF‐1α total amount in GCF were also higher in periodontitis groups compared with the control group ( P  < 0.05). GCF total VEGF‐A content was significantly higher in the GAgP group compared with the CP and the controls (respectively; P  = 0.023, P  = 0.003). There was a significant correlation between ADAMTS‐1, VEGF‐A, and HIF‐1α levels in the GCF and clinical periodontal parameters (probing depth [PD], bleeding on probing [BOP], and clinical attachment loss (CAL); P  < 0.05). Conclusion: ADAMTS‐1 may play a role in advanced periodontal disease pathogenesis in correlation with tissue hypoxia and vascularization.